Control Program of Two-fingered Dexterous Manipulation with Primitive Motions - Sasaki, K.; Hwang, C.-S. (IEEE International Conference on Intelligent Robots and Systems, 2003)
This paper presents a motion planning and control method for the dexterous manipulation with a robotic hand. For a given trajectory of an object, a simulation system calculates the A8741735necessary joint displacements and contact forces at the fingertips. These joint displacements and contact forces are the reference inputs to the control loops of the robotic fingers. A task is decomposed into a set of primitive motions, and each primitive motion is executed using the output of the simulation system as the reference. Force sensors and dynamic tactile sensors are used to adapt to uncertainties encountered during manipulation. Several experimental results are presented.